2009
DOI: 10.1093/cercor/bhp142
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processing during Older Adults' Comprehension of Spoken Sentences: Age Differences in Resource Allocation and Connectivity

Abstract: Speech comprehension remains largely preserved in older adults despite significant age-related neurophysiological change. However, older adults' performance declines more rapidly than that of young adults when listening conditions are challenging. We investigated the cortical network underlying speech comprehension in healthy aging using short sentences differing in syntactic complexity, with processing demands further manipulated through speech rate. Neural activity was monitored using blood oxygen level-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
197
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(232 citation statements)
references
References 77 publications
28
197
6
1
Order By: Relevance
“…To our knowledge, very few studies have found or interpreted differences between young and older healthy adults in this region during a semantic task (Berlingeri, et al, 2010;Peelle, et al, 2010). Consistent with our own findings, Ansado et al (2013) found a pattern of hyperactivation in the bilateral temporal pole for older adults during a semantic judgment task on visually-presented words using fMRI.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…To our knowledge, very few studies have found or interpreted differences between young and older healthy adults in this region during a semantic task (Berlingeri, et al, 2010;Peelle, et al, 2010). Consistent with our own findings, Ansado et al (2013) found a pattern of hyperactivation in the bilateral temporal pole for older adults during a semantic judgment task on visually-presented words using fMRI.…”
supporting
confidence: 86%
“…Both of these regions have been reported to play a key role in semantic control processes (Jefferies, 2013;Noonan, et al, 2013;Whitney, Kirk, O'Sullivan, Lambon Ralph, & Jefferies, 2012). Other studies have also reported greater recruitment of temporoparietal regions during semantic processing in normal aging (Grossman, et al, 2002;Nielson, et al, 2006;Peelle, et al, 2010). Grossman et al (2002) concluded that greater activation in the right posterolateral temporoparietal regions for older adults during a sentence comprehension task may reflect a compensatory mechanism enabling older adults to maintain sentence comprehension at the same level as younger adults.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This point is problematic for studies that modeled sentence duration into the stipulated neural profile of activation before convolution with the HRF (Adank and Devlin, 2010); this choice surreptitiously amounts to assuming a linear dependency of brain activity with duration and only allows the experimenters to discover brain areas that deviate from this ideal pattern. Other studies do not describe how they addressed this issue (Peelle et al, 2004(Peelle et al, , 2010 or introduce confounds in their block design by having more sentences per unit of time in blocks with faster compression rates (Poldrack et al, 2001).…”
Section: Image Acquisition and Analysismentioning
confidence: 99%
“…Unlike previous fMRI studies of speech compression that used block designs (Poldrack et al, 2001;Peelle et al, 2004Peelle et al, , 2010Adank and Devlin, 2010), we used a slow event-related design to measure the fMRI response to a single sentence, thus allowing us to determine whether cortical processing speed, indexed by the phase of the fMRI response, accelerates when the stimulus is speeded; which regions show a sudden collapse of activation in parallel to the sudden loss of intelligibility at fast presentation rates; and how these effects differ for spoken and written language.…”
Section: Introductionmentioning
confidence: 99%